ATRT-08. SMARCB1- and SMARCA4-deficient malignant brain tumors with complex copy number alterations andTP53 mutations may represent the first clinical manifestation of Li-Fraumeni syndrome. (3rd June 2022) - Hasselblatt, Martin; Thomas, Christian; Federico, Aniello; Nemes, Karolina; Johann, Pascal D; Bison, Brigitte; Bens, Susanne; Kordes, Uwe; Redlich, Antje; Lessel, Lienhard; Pajtler, Kristian W; Mawrin, Christian; et al.
Abstract: Atypical teratoid/rhabdoid tumor (AT/RT) is a malignant central nervous system tumor predominantly affecting infants. Mutations of SMARCB1 or (rarely) SMARCA4 causing loss of nuclear SMARCB1 or SMARCA4 protein expression are characteristic features, but further recurrent genetic alterations are lacking. Most AT/RTs occur de novo, but secondary AT/RTs arising in other central nervous system tumors have been reported. Malignant gliomas, IDH-wildtype, arising in patients with Li-Fraumeni syndrome typically show somatic mutations of TP53 as well as complex copy number alterations, but little is known about loss of SMARCB1 or SMARCA4 protein expression in this context. Here we report two children, in whom malignant supratentorial brain tumors with SMARCB1-deficiency, complex copy number alterations and somatic TP53 mutations lead to the discovery of pathogenic/likely pathogenic TP53 variants in the germ line. Screening of the molecularneuropathology.org data set for cases with similar genetic and epigenetic alterations yielded another case with SMARCA4-deficiency in a young adult with Li-Fraumeni syndrome. In conclusion, SMARCB1- or SMARCA4-deficient malignant brain tumors with complex copy number alterations and somatic TP53 mutations in children and young adults may represent the first clinical manifestation of Li-Fraumeni syndrome and should prompt genetic counseling and investigation for TP53 germline status.